The Application of SOSA Bottle to Reduce The Pulmonary TB Transmission in Tanjung Gusta Penitentiary (Journal of Saintech Transfer, 2022)
The prevalence of pulmonary Tuberculosis (TB) in penitentiaries is 3 times higher compared to the general population. Reviono (2016), TB ranks in the 4th among the most common illnesses suffered by prisoners and is the major cause of morbidity and death in penitentiaries and detention centers in Indonesia. Sarumpaet and Syarifah (2018) posit the effectiveness of using SOSA (Sori-Syarifah) bags compared to SOSA bottles including 5% of Chlorophen accompanied by masks, tissues in cutting off the transmission of pulmonary TB with Acid Fast Bacilli (AFB+). SOSA bottles is significantly more effective (p